PIV measurements using refraction at a solid–fluid interface. (17th December 2020) - Cabut, Damien; Michard, Marc; Simoëns, Serge; Todoroff, Violaine; Hermange, Corentin; Le-Chenadec, Yohan
Abstract: Laser light sheet refraction at the fluid flow–window interface is proposed to perform fluorescent particle image velocimetry (PIV) measurements, in particular for cases in which optical access limits the possibilities of illuminating a flow with a planar collimated light sheet. The study of laser sheet propagation in the present measurement method is led by ray tracing to quantify the illumination intensity. To describe the limitations of this developed PIV version (refracted PIV (R-PIV)), we proposed a cross-correlation model (CCM) for analyzing image pairs that is an extension of the models used in the cases of µ-PIV or planar PIV (P-PIV) techniques. This CCM accounts for the R-PIV optical constraints of (1) in-depth and longitudinal inhomogeneities of the light sheet refraction at the location of the object plane or (2) integration in depth of the fluorescence from seeding particles. This R-PIV and the P-PIV techniques are further compared in the case of an academic pipe flow for which the analytic solution is known. Our extended CCM function is finally applied, given the theoretical flow velocity, the flow illumination and the seeding flow parameters, to analyze error levels in determining the real flow velocity field.